Soft rock electrochemical modification experiment device and method based on ionic liquid
By using ionic liquid as the electrolyte in soft rock electrochemical modification and combined with pressurized liquid injection technology, the problem of soft rock hydration disintegration and long electrochemical modification time period is solved, and a more efficient electrochemical modification effect of soft rock is achieved.
Patent Information
- Application Number
- CN202510082190.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-20
AI Technical Summary
In the existing electrochemical modification methods of soft rocks, the salt solution causes the soft rock to hydrate and disintegrate, and the time period required for electrochemical modification to reinforce the soft rocks is relatively long, which is a contradiction.
An ionic liquid is used as the electrolyte, and an experimental device for in-situ electrochemically modified soft rocks is developed to achieve synchronous operation of pressurized injection of the electrolyte and electrochemical modification of the soft rocks.
It effectively solves the problem of hydration and disintegration of soft rocks during electrochemical modification of soft rocks, improves the electrochemical modification effect, and realizes the coordinated progress of electrochemical modification and pressurized liquid injection, which is closer to the actual situation of the project.
Smart Images

Figure CN119738465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft rock electrochemical modification experiments, and in particular to an ionic liquid-based soft rock electrochemical modification experiment device and method. Background Art
[0002] In coal-bearing strata, the stability control of soft rock has always troubled the production and construction of coal mines. The engineering problems caused by soft rock are the result of the continuous deterioration of rock mass quality under the action of hydration or weathering. The basic theoretical research on engineering control of soft rock stability is a key scientific problem that urgently needs to be solved in coal mine production and construction. In engineering, the methods of supporting and reinforcing soft rock include anchor spraying reinforcement, strong shed support, masonry arch or closed concrete arch, and various support methods produced by combining these methods to ensure the stability and safety of mudstone engineering. However, these methods are all considered from the perspective of force balance, and are not considered from the perspective of improving the physical and chemical properties and mechanical properties of the soft rock itself. Moreover, the engineering reinforced by the above methods can often only be maintained for a period of time and needs to be repaired frequently. Moreover, the amount of repair work, the cost and the impact on production are very large. Therefore, it is very necessary to find a method to achieve long-term stability of soft rock engineering by changing the physical and chemical properties and mechanical properties of the soft rock itself.
[0003] Electrochemical modification of soft rock is a technical method to change the physical, chemical and mechanical properties of soft rock itself to achieve long-term stability of soft rock engineering. Electrochemical modification of soft rock is to apply a low-voltage DC electric field to the soft rock mass. Under the action of the electric field, exchangeable cations, tiny charged particles and polar water molecules in the rock mass migrate in a directional manner, causing irreversible changes in the chemical properties of the fluid in the pores and fissures of the rock mass, the mineral double electric layer, the matrix and the pore and fissure structure, which in turn leads to changes in the mechanical and engineering properties of the rock mass. Due to its low disturbance and effectiveness to the rock mass, this technical method has received increasing attention.
[0004] The principle of electrochemical modification of soft rock is as follows:
[0005] The basic principle of electrochemical modification of soft rock is electro-osmosis, electrophoresis and other electrokinetic phenomena. Electro-osmosis causes more water molecules in the pores of soft rock to move toward the cathode, because in the double electric layer on the surface of clay mineral particles, the positively charged ions in the diffusion layer are replaced by the positively charged ions in the electrolyte, carrying more water molecules to move toward the cathode, which reduces the hydration layer on the surface of clay particles, reduces hydrophilicity, and dehydrates and consolidates the area near the anode; the intermolecular force and hydrogen bond force increase, the cohesive force increases, and the clay minerals in the soft rock undergo a crystallization process. In soft rock, the surface of clay mineral particles carries a negative charge. Under the action of electrophoresis, the negatively charged clay mineral particles move toward the anode and are enriched, causing the fine component particles in the pores to agglomerate and become coarser, and the particle size increases. After the electrochemical action, the clay mineral content of the soft rock decreases and new minerals are generated. The electrokinetic phenomenon strengthens the connection between clay mineral particles in soft rock, and the cations form hydroxide precipitation on the surface of clay mineral particles in the pores to fill the pores of the soft rock, thereby improving its mechanical properties.
[0006] At present, the existing technical solutions to the problem are: anchor spraying reinforcement, strong shed support, masonry, closed concrete arch and other traditional soft rock support reinforcement methods. Most of the research focuses on the reinforcement of broken or softened and disintegrated mudstone. It is only reinforced from the perspective of force balance, and the stability control of mudstone engineering is achieved by changing the external factors of mudstone. There are many limitations and timeliness. The electrochemical modification method of soft rock can overcome the shortcomings of traditional soft rock support reinforcement methods, but the electrolyte used in the existing soft rock electrochemical modification method is NaCl, CaCl2, CuCl2 and other salt solutions, and soft rock has the characteristic of disintegrating when exposed to water. The time period required for electrochemical modification and reinforcement of soft rock is relatively long, and there is a contradiction between the positive effect of electrochemical reinforcement and the reverse effect of soft rock hydration and disintegration during the electrochemical modification process. Moreover, in the existing electrochemical modification and reinforcement technology for soft rock, the electrolyte and the soft rock are in contact at normal pressure. In order to actually perform electrochemical reinforcement on the rock mass, the electrolyte must be injected under pressure. Therefore, we propose an experimental device for electrochemical modification of soft rock based on ionic liquid. Summary of the invention
[0007] The purpose of the present invention is to provide an ionic liquid-based soft rock electrochemical modification experimental device to solve the problems raised in the above background technology.
[0008] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: an ionic liquid-based soft rock electrochemical modification experimental device, comprising a water container, a piston container and an electrochemical modification tank, wherein the piston container is arranged on one side of the water container, and the piston container is composed of a first upper cover, a base, a cylinder and a piston body, the electrochemical modification tank is arranged on one side of the piston container, the electrochemical modification tank comprises a second upper cover and a tank body, a soft rock sample is installed inside the tank body, and an iron perforated metal cathode and an iron perforated metal anode are respectively installed at the top and bottom ends of the soft rock sample, a plunger metering pump, a pressure sensor, a first stop valve and a first pressure gauge are respectively arranged between the water container and the piston container, a voltage-stabilized DC power supply, a third stop valve and a second stop valve are arranged between the piston container and the electrochemical modification tank, and a second pressure gauge, a fourth stop valve, a third pressure gauge and a vacuum pump are respectively arranged on one side of the electrochemical modification tank.
[0009] Preferably, the water container is connected to a plunger metering pump via a pipeline.
[0010] Preferably, the plunger metering pump is connected to the pressure sensor, the first stop valve, and the first pressure gauge in sequence and then connected to the first upper cover.
[0011] Preferably, the cylinder is connected to the first upper cover and the base through threads, the piston body and the cylinder are in close sliding contact, and the base is connected to the tank body through a pipeline via a third stop valve.
[0012] Preferably, the soft rock sample fits tightly with the ferrous perforated metal anode and the ferrous perforated metal cathode, the tank body is connected to the second upper cover by threads, the second upper cover is connected to the second pressure gauge, the fourth stop valve, and the third pressure gauge in sequence through pipelines and then connected to the vacuum pump.
[0013] Preferably, the stabilized direct current is connected to an iron perforated metal anode and an iron perforated metal cathode through a conductor to provide electrical energy for the soft rock specimen.
[0014] Preferably, the pressure sensor, the first pressure gauge, the second pressure gauge, the third pressure gauge, the fourth stop valve, and the vacuum pump constitute a pressure control and monitoring system for controlling and monitoring the pressure of the experimental system.
[0015] Preferably, the tank body is made of a transparent insulating material.
[0016] An ionic liquid-based soft rock electrochemical modification experimental method comprises the following steps: first, drilling a hole with a diameter and a depth of 5 mm at the center of the bottom end of a 50×100 mm standard cylindrical soft rock sample; second, placing the sample in an electrochemical modification tank, placing an electrolyte injection tube in the hole at the center of the bottom end of the soft rock sample, installing an iron metal anode with holes and an iron metal cathode with holes, connecting wires, sealing the electrochemical modification tank, connecting a fourth stop valve, a third pressure gauge and a vacuum pump, closing the valve between the electrochemical modification tank and a piston container, adding electrolyte to the piston container, sealing the piston container, connecting a first pressure gauge, a first stop valve, a pressure sensor, and a plunger metering pump, opening the fourth stop valve, and starting the vacuum pump to perform electrochemical modification. The first step is to evacuate the tank; the third step is to close the fourth stop valve after the evacuation, open the first stop valve and the third stop valve, and start the plunger metering pump to inject electrolyte into the cylindrical soft rock sample; the fourth step is to apply a DC voltage to the cylindrical soft rock sample, start the pressurized injection and the soft rock electrochemical modification synchronization experiment, when the electrolyte rises to 5mm from the upper end of the soft rock sample, stop the pressurized injection operation, and continue to keep the power on for 72h; the fifth step is to close the first stop valve and the third stop valve, open the second stop valve on the electrolyte discharge pipeline at the bottom of the electrochemical modification tank, discharge the electrolyte in the electrochemical modification tank, and then take out the cylindrical soft rock sample. After vacuum drying, use a universal testing machine to perform a Brazilian splitting test on the specimen to calculate the tensile strength.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention adopts ionic liquid as electrolyte, effectively solving the problem of soft rock hydration and disintegration in the process of electrochemical modification of soft rock. In view of the defect that water in salt solution causes soft rock to soften and disintegrate in the process of soft rock modification using salt solution as electrolyte, the present invention adopts ionic liquid as electrolyte, effectively solving the problem of soft rock hydration and disintegration in the process of electrochemical modification of soft rock. Ionic liquid has the advantages of low vapor pressure, high conductivity, high electrochemical stability and strong designability, which can fully meet the requirements of electrolyte required for electrochemical modification. When ionic liquid is used as electrolyte for electrochemical modification, it is in direct contact with electrodes, has low impedance, and has good diffusivity and fluidity of active substances and additives. Ionic liquid is a liquid composed entirely of ions, which is a salt in liquid state at low temperature (<100°C), does not contain water, avoids the characteristics of soft rock absorbing water, swelling, softening and disintegrating, and has a more significant effect on electrochemical modification. The present invention develops an experimental device for in-situ electrochemical modification of soft rock, which realizes the simultaneous pressurized injection of electrolyte and electrochemical modification of soft rock. In view of the defects of the existing electrochemical modification and reinforcement of soft rock technology methods in which electrolyte is injected into the soft rock mass without pressure, the present invention has developed an experimental device for the coordinated injection of electrolyte under pressure and electrochemical modification of soft rock, realizing the integration of pressurized injection and electrochemical modification of soft rock, and improving the technical method of electrochemical modification of soft rock. In summary, the present invention effectively solves the problem of hydration and disintegration of soft rock in the conventional electrochemical modification of soft rock using salt solution as electrolyte. The experimental device for in-situ electrochemical modification of soft rock involved in the present invention can realize the coordinated injection of electrolyte under pressure and electrochemical modification of soft rock, which is closer to engineering practice. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a structural principle diagram of the present invention;
[0020] Figure 2 It is a schematic diagram of the enlarged structure of the piston container of the present invention;
[0021] Figure 3 It is a schematic diagram of the enlarged structure of the electrochemical modification tank of the present invention;
[0022] Figure 4 It is a schematic structural diagram of the piston container pressure control and monitoring system of the present invention;
[0023] Figure 5 It is a schematic diagram of the structure of the electrochemical modification tank pressure control and monitoring system of the present invention.
[0024] In the figure: 1. water container; 2. plunger metering pump; 3. pressure sensor; 4. first stop valve; 5. first pressure gauge; 6. first upper cover; 7. cylinder; 8. piston body; 9. base; 10. second stop valve; 11. third stop valve; 12. regulated DC power supply; 13. second pressure gauge; 14. iron metal anode with holes; 15. soft rock sample; 16. tank body; 17. iron metal cathode with holes; 18. second upper cover; 19. fourth stop valve; 20. third pressure gauge; 21. vacuum pump; 22. piston container; 23. electrochemical modification tank. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. All other embodiments obtained by ordinary technicians in the field without making creative work based on the embodiments of the present invention shall fall within the scope of protection of the present invention.
[0027] See also Figure 1-5 , an embodiment provided by the present invention: an ionic liquid-based soft rock electrochemical modification experimental device, comprising a water container 1, a piston container 22 and an electrochemical modification tank 23, wherein the piston container 22 is arranged on one side of the water container 1, and the piston container 22 is composed of a first upper cover 6, a base 9, a cylinder 7 and a piston body 8, and the electrochemical modification tank 23 is arranged on one side of the piston container 22, and the electrochemical modification tank 23 comprises a second upper cover 18 and a tank body 16, a soft rock sample 15 is installed inside the tank body 16, and an iron perforated metal cathode 17 and an iron perforated metal anode 14 are installed at the top and bottom of the soft rock sample 15 respectively;
[0028] A plunger metering pump 2, a pressure sensor 3, a first stop valve 4, and a first pressure gauge 5 are respectively arranged between the water container 1 and the piston container 22;
[0029] A voltage-stabilized DC power supply 12, a third stop valve 11, and a second stop valve 10 are provided between the piston container 22 and the electrochemical modification tank 23;
[0030] A second pressure gauge 13, a fourth stop valve 19, a third pressure gauge 20, and a vacuum pump 21 are respectively provided on one side of the electrochemical modification tank 23;
[0031] The water container 1 is connected to the plunger metering pump 2 through a pipeline;
[0032] The plunger metering pump 2 is connected to the pressure sensor 3, the first stop valve 4, the first pressure gauge 5 in sequence, and then connected to the first upper cover 6;
[0033] The cylinder 7 is connected to the first upper cover 6 and the base 9 by threads, the piston body 8 is in close sliding contact with the cylinder 7, and the base 9 is connected to the tank 16 through a pipeline via the third stop valve 11;
[0034] The soft rock sample 15 is tightly fitted with the iron perforated metal anode 14 and the iron perforated metal cathode 17, the tank body 16 is connected with the second upper cover 18 by threads, and the second upper cover 18 is connected with the second pressure gauge 13, the fourth stop valve 19, and the third pressure gauge 20 in sequence through pipelines, and then connected with the vacuum pump 21;
[0035] The voltage-stabilized DC power supply 12 is connected to the iron perforated metal anode 14 and the iron perforated metal cathode 17 through a wire;
[0036] The pressure sensor 3, the first pressure gauge 5, the second pressure gauge 13, the third pressure gauge 20, the fourth stop valve 19, and the vacuum pump 21 constitute a pressure control and monitoring system for controlling and monitoring the pressure of the experimental system;
[0037] The tank body 16 is made of a transparent insulating material;
[0038] Specifically, the experimental method for integrating pressurized liquid injection and electrochemical modification of soft rock is as follows: a hole with a diameter and a depth of 5 mm is drilled at the center of the bottom end of the prepared 50×100 mm standard cylindrical soft rock sample 15, and then the sample is placed in the electrochemical modification tank 23, and the electrolyte injection tube is placed in the hole at the center of the bottom end of the soft rock sample 15, and the iron perforated metal anode 14 and the iron perforated metal cathode 17 are installed, and the wires are connected, the electrochemical modification tank 23 is sealed, the fourth stop valve 19, the third pressure gauge 20 and the vacuum pump 21 are connected, and the valve between the electrochemical modification tank 23 and the piston container 22 is closed, and the electrolyte is added to the piston container 22. In the process, seal the piston container 22, connect the first pressure gauge 5, the first stop valve 4, the pressure sensor 3, and the plunger metering pump 2, open the fourth stop valve 19, and start the vacuum pump 21 to evacuate the electrochemical modification tank. After the evacuation is completed, close the fourth stop valve 19, open the first stop valve 4 and the third stop valve 11, and start the plunger metering pump 2 to inject electrolyte into the cylindrical soft rock sample 15. At the same time, apply a DC voltage to the cylindrical soft rock sample 15, start the pressurized injection and soft rock electrochemical modification synchronization experiment, and when the electrolyte rises to 5 mm from the upper end of the soft rock sample 15, stop the pressurized injection operation and continue to keep the power on for 72 hours;
[0039] After the experiment, the first stop valve 4 and the third stop valve 11 are closed, and the second stop valve 10 on the electrolyte discharge pipeline at the bottom of the electrochemical modification tank 23 is opened to discharge the electrolyte in the electrochemical modification tank 23, and then the cylindrical soft rock sample 15 is taken out, and after vacuum drying, the Brazilian splitting test is performed on the sample using a universal testing machine to calculate the tensile strength;
[0040] The present invention adopts ionic liquid as electrolyte, effectively solving the problem of soft rock hydration and disintegration in the process of electrochemical modification of soft rock. In view of the defect that water in salt solution causes soft rock to soften and disintegrate in the process of soft rock modification using salt solution as electrolyte, the present invention adopts ionic liquid as electrolyte, effectively solving the problem of soft rock hydration and disintegration in the process of electrochemical modification of soft rock. Ionic liquid has the advantages of low vapor pressure, high conductivity, high electrochemical stability and strong designability, which can fully meet the requirements of electrolyte required for electrochemical modification. When ionic liquid is used as electrolyte for electrochemical modification, it is in direct contact with electrodes, has low impedance, and has good diffusivity and fluidity of active substances and additives. Ionic liquid is a liquid composed entirely of ions, which is a salt in liquid state at low temperature (<100°C), does not contain water, avoids the characteristics of soft rock absorbing water, swelling, softening and disintegrating, and has a more significant effect on electrochemical modification. The present invention develops an experimental device for in-situ electrochemical modification of soft rock, which realizes the simultaneous pressurized injection of electrolyte and electrochemical modification of soft rock. Aiming at the defect of the existing electrochemical modification and reinforcement technology of soft rock, which is the non-pressurized injection of electrolyte into the soft rock mass, the pressurized injection and the electrochemical modification of soft rock are integrated to improve the technical method of electrochemical modification of soft rock. In summary, the present invention effectively solves the problem of hydration and disintegration of soft rock in the conventional electrochemical modification of soft rock using salt solution as electrolyte. The experimental device for in-situ electrochemical modification of soft rock involved in the present invention can realize the coordinated pressurized injection of electrolyte and the electrochemical modification of soft rock, which is closer to engineering practice.
[0041] Soft rock modification effect
[0042] Implementation plan 1: Using 1 mol / L imidazole ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution as the electrolyte, under the conditions of injection pressure of 0.15Mpa and potential gradient of 1.0V / cm, pressurized injection and soft rock electrochemical modification synchronous experiments were carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 3.82Mpa, which was 5.82% higher than the tensile strength of the original soft rock specimen before modification of 3.61Mpa.
[0043] Implementation Plan 2: Using 1 mol / L imidazole ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate aqueous solution as the electrolyte, under the conditions of injection pressure of 0.15Mpa and potential gradient of 1.0V / cm, a pressurized injection and soft rock electrochemical modification synchronous experiment was carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 3.91Mpa, which was 8.31% higher than the tensile strength of the original soft rock specimen before modification of 3.61Mpa.
[0044] Implementation Plan 3: Using 1.5mol / L imidazole ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate aqueous solution as the electrolyte, under the conditions of injection pressure of 0.15Mpa and potential gradient of 1.0V / cm, a pressurized injection and soft rock electrochemical modification synchronous experiment was carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 3.99Mpa, which was 10.53% higher than the tensile strength of the original soft rock specimen before modification of 3.61Mpa.
[0045] Implementation Plan 4: Using 0.5 mol / L imidazole ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution as the electrolyte, under the conditions of injection pressure of 0.15 MPa and potential gradient of 1.0 V / cm, a pressurized injection and soft rock electrochemical modification synchronous experiment was carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 3.74 MPa, which was 3.60% higher than the tensile strength of the original soft rock specimen before modification of 3.61 MPa.
[0046] Implementation Plan 5: Using 1.5mol / LCuCl2 aqueous solution as the electrolyte, under the conditions of injection pressure of 0.15Mpa and potential gradient of 1.0V / cm, a pressurized injection and soft rock electrochemical modification synchronous experiment was carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 3.37Mpa, which was 6.65% lower than the tensile strength of the original soft rock specimen before modification of 3.61Mpa.
[0047] Implementation Plan 6: Using pure imidazole ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate as the electrolyte, under the conditions of injection pressure of 0.15Mpa and potential gradient of 1.0V / cm, a pressurized injection and soft rock electrochemical modification synchronous experiment was carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 4.56Mpa, which was 26.32% higher than the tensile strength of the original soft rock specimen before modification of 3.61Mpa; compared with the tensile strength of the soft rock specimen after electrochemical modification in 1.5mol / LCuCl2 aqueous solution of 3.37Mpa, it was 35.31% higher.
[0048] Implementation Plan 7: Using pure imidazole ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate as the electrolyte, under the conditions of injection pressure of 0.15Mpa and potential gradient of 1.0V / cm, a pressurized injection and soft rock electrochemical modification synchronous experiment was carried out. After completing the electrochemical modification and vacuum drying, a universal testing machine was used to conduct a Brazilian splitting test on the specimen to obtain the load-displacement curve of the specimen. The tensile strength of the specimen was calculated to be 4.69Mpa, which was 29.92% higher than the tensile strength of the original soft rock specimen before modification of 3.61Mpa; compared with the tensile strength of the soft rock specimen after electrochemical modification in 1.5mol / LCuCl2 aqueous solution of 3.37Mpa, it was 39.17% higher.
[0049] When the embodiment of the present application is used: First, the device is mainly composed of a liquid injection system, an electrochemical modification system, and a pressure control and monitoring system. The liquid injection system for pressurizing electrolyte into soft rock samples includes a water container 1 for containing a water medium providing injection pressure, a plunger metering pump 2 for providing injection pressure, a first stop valve 4, a third stop valve 11, and a piston container 22 for containing electrolyte, and the piston container 22 is composed of a first upper cover 6, a base 9, a cylinder 7 and a piston body 8; the electrochemical modification system for electrochemical modification of soft rock includes a device for installing a soft rock sample 15, an electrochemical modification tank 23 (a second upper cover 18 and a tank body 16), a voltage-stabilized DC power supply 12 for providing electric energy to the soft rock specimen, an iron perforated metal anode 14, an iron perforated metal cathode 17, and a second stop valve 10 for discharging electrolyte; the pressure control and monitoring system for controlling and monitoring the pressure of the experimental system includes a pressure sensor 3, a first pressure gauge 5, a second pressure gauge 13, a third pressure gauge 20, a fourth stop valve 19, and a vacuum pump 21. The connection method is as follows: the water container 1 is connected to the plunger metering pump 2 through a pipeline, the plunger metering pump 2 is connected to the pressure sensor 3, the first stop valve 4, and the first pressure gauge 5 in sequence, and then connected to the piston container 22 through the first upper cover 6, the cylinder 7 is connected to the first upper cover 6 and the base 9 is threaded, the piston body 8 and the cylinder 7 are in close sliding contact, and the base 9 is connected to the tank body 16 through the pipeline through the third stop valve 11; the voltage-stabilized DC power supply 12 is connected to the iron perforated metal anode 14 and the iron perforated metal cathode 17 through a wire, the soft rock sample 15 is tightly fitted with the iron perforated metal anode 14 and the iron perforated metal cathode 17, and then placed at the bottom of the tank body 16, the tank body 16 is connected to the second upper cover 18 through a thread, the second upper cover 18 is connected to the second pressure gauge 13, the fourth stop valve 19, and the third pressure gauge 20 in sequence through a pipeline, and then connected to the vacuum pump 21;
[0050] The experimental method for integrating pressurized liquid injection and electrochemical modification of soft rock is as follows: a hole with a diameter and a depth of 5 mm is drilled at the center of the bottom end of the prepared 50×100 mm standard cylindrical soft rock sample 15, and then the sample is placed in the electrochemical modification tank 23, and the electrolyte injection tube is placed in the hole at the center of the bottom end of the soft rock sample 15, and the iron perforated metal anode 14 and the iron perforated metal cathode 17 are installed, and the wires are connected, the electrochemical modification tank 23 is sealed, the fourth stop valve 19, the third pressure gauge 20 and the vacuum pump 21 are connected, and the valve between the electrochemical modification tank 23 and the piston container 22 is closed, and the electrolyte is added to the piston container 22. The piston container 22 is sealed, the first pressure gauge 5, the first stop valve 4, the pressure sensor 3, and the plunger metering pump 2 are connected, the fourth stop valve 19 is opened, and the vacuum pump 21 is turned on to evacuate the electrochemical modification tank. After the evacuation is completed, the fourth stop valve 19 is closed, the first stop valve 4 and the third stop valve 11 are opened, and the plunger metering pump 2 is turned on to inject electrolyte into the cylindrical soft rock sample 15. At the same time, a DC voltage is applied to the cylindrical soft rock sample 15, and the pressurized injection and the soft rock electrochemical modification synchronization experiment are started. When the electrolyte rises to 5 mm from the upper end of the soft rock sample 15, the pressurized injection operation is stopped, and the power-on state is maintained for 72 hours. After the experiment, the first stop valve 4 and the third stop valve 11 are closed, and the second stop valve 10 on the electrolyte discharge pipeline at the bottom of the electrochemical modification tank 23 is opened to discharge the electrolyte in the electrochemical modification tank 23, and then the cylindrical soft rock sample 15 is taken out. After vacuum drying, the specimen is subjected to a Brazilian splitting test using a universal testing machine to calculate the tensile strength.
[0051] The present invention adopts ionic liquid as electrolyte, effectively solving the problem of soft rock hydration and disintegration in the process of electrochemical modification of soft rock. In view of the defect that water in salt solution causes soft rock to soften and disintegrate in the process of soft rock modification using salt solution as electrolyte, the present invention adopts ionic liquid as electrolyte, effectively solving the problem of soft rock hydration and disintegration in the process of electrochemical modification of soft rock. Ionic liquid has the advantages of low vapor pressure, high conductivity, high electrochemical stability and strong designability, which can fully meet the requirements of electrolyte required for electrochemical modification. When ionic liquid is used as electrolyte for electrochemical modification, it is in direct contact with electrodes, has low impedance, and has good diffusivity and fluidity of active substances and additives. Ionic liquid is a liquid composed entirely of ions, which is a salt in liquid state at low temperature (<100°C), does not contain water, avoids the characteristics of soft rock absorbing water, swelling, softening and disintegrating, and has a more significant effect on electrochemical modification. The present invention develops an experimental device for in-situ electrochemical modification of soft rock, which realizes the simultaneous pressurized injection of electrolyte and electrochemical modification of soft rock. Aiming at the defect of the existing electrochemical modification and reinforcement of soft rock technology that the electrolyte is injected into the soft rock mass without pressure, the pressurized injection and the electrochemical modification of soft rock are integrated to improve the technical method of electrochemical modification of soft rock. In summary, the present invention effectively solves the problem of hydration and disintegration of soft rock in the conventional electrochemical modification of soft rock using salt solution as electrolyte. The experimental device for in-situ electrochemical modification of soft rock involved in the present invention can realize the coordinated pressurized injection of electrolyte and the electrochemical modification of soft rock, which is closer to engineering practice.
[0052] Obviously, the above-described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. An experimental device for electrochemical modification of soft rocks based on ionic liquids, characterized in that: The invention comprises a water container (1), a piston container (22) and an electrochemical modification tank (23), wherein the piston container (22) is arranged on one side of the water container (1), and the piston container (22) is composed of a first upper cover (6), a base (9), a cylinder (7) and a piston body (8), and the electrochemical modification tank (23) is arranged on one side of the piston container (22), and the electrochemical modification tank (23) comprises a second upper cover (18) and a tank body (16), a soft rock sample (15) is installed inside the tank body (16), and iron is installed at the top and bottom of the soft rock sample (15) respectively. A perforated metal cathode (17) and an iron perforated metal anode (14); a plunger metering pump (2), a pressure sensor (3), a first stop valve (4), and a first pressure gauge (5) are respectively arranged between the water container (1) and the piston container (22); a voltage-stabilized DC power supply (12), a third stop valve (11), and a second stop valve (10) are arranged between the piston container (22) and the electrochemical modification tank (23); and a second pressure gauge (13), a fourth stop valve (19), a third pressure gauge (20), and a vacuum pump (21) are respectively arranged on one side of the electrochemical modification tank (23).
2. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The water container (1) is connected to the plunger metering pump (2) via a pipeline.
3. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The plunger metering pump (2) is connected to the pressure sensor (3), the first stop valve (4), and the first pressure gauge (5) in sequence and then connected to the first upper cover (6).
4. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The cylinder (7) is connected to the first upper cover (6) and the base (9) by threads, the piston body (8) and the cylinder (7) are in close sliding contact, and the base (9) is connected to the tank body (16) through a pipeline via a third stop valve (11).
5. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The soft rock sample (15) is tightly fitted with the iron perforated metal anode (14) and the iron perforated metal cathode (17); the tank body (16) is connected to the second upper cover (18) by threads; the second upper cover (18) is connected to the second pressure gauge (13), the fourth stop valve (19), and the third pressure gauge (20) in sequence through pipelines, and then connected to the vacuum pump (21).
6. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The voltage-stabilized DC power supply (12) is connected to an iron perforated metal anode (14) and an iron perforated metal cathode (17) via a conductor.
7. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The pressure sensor (3), the first pressure gauge (5), the second pressure gauge (13), the third pressure gauge (20), the fourth stop valve (19), and the vacuum pump (21) constitute a pressure control and monitoring system for controlling and monitoring the pressure of the experimental system.
8. The soft rock electrochemical modification experimental device based on ionic liquid according to claim 1, characterized in that: The tank body (16) is made of a transparent insulating material.
9. An experimental method for electrochemical modification of soft rocks based on ionic liquids, characterized in that: The first step is to drill a hole with a diameter and a depth of 5 mm at the center of the bottom end of the prepared 50×100 mm standard cylindrical soft rock sample (15); the second step is to place it in an electrochemical modification tank (23), place an electrolyte injection tube in the hole at the center of the bottom end of the soft rock sample (15), install an iron metal anode with holes (14) and an iron metal cathode with holes (17), connect the wires, seal the electrochemical modification tank (23), connect the fourth stop valve (19), the third pressure gauge (20) and the vacuum pump (21), close the valve between the electrochemical modification tank (23) and the piston container (22), add the electrolyte into the piston container (22), seal the piston container (22), connect the first pressure gauge (5), the first stop valve (4), the pressure sensor (3), and the plunger metering pump (2), open the fourth stop valve (19), and start the vacuum pump (21) to energize the electrochemical modification tank (23). The modification tank is evacuated; the third step is to close the fourth stop valve (19) after the evacuation is completed, open the first stop valve (4) and the third stop valve (11), and start the plunger metering pump (2) to inject electrolyte into the cylindrical soft rock sample (15); the fourth step is to apply a DC voltage to the cylindrical soft rock sample (15), start the pressurized injection and the soft rock electrochemical modification synchronous experiment, and when the electrolyte rises to 5 mm from the upper end of the soft rock sample (15), stop the pressurized injection operation, and continue to maintain the power-on state for 72 hours; the fifth step is to close the first stop valve (4) and the third stop valve (11), open the second stop valve (10) on the electrolyte discharge pipeline at the bottom of the electrochemical modification tank (23), discharge the electrolyte in the electrochemical modification tank (23), and then take out the cylindrical soft rock sample (15), and after vacuum drying, use a universal testing machine to perform a Brazilian splitting test on the specimen to calculate the tensile strength.
Citation Information
Patent Citations
Test method of changing performances of rock
CN101644637A
Temperature and pressure controllable ultrasonic monitoring device and method for thick oil saturated rock sample
CN113340993A
HTHP CO2-fluid-rock surface property measurement system and the measurement method
KR102596251B1